Dental health during pregnancy – and beyond. (2nd February 2021) - Russell, Marisa; Grimwood, Heidi
Abstract : Marisa Russell and Heidi Grimwood explain why a new pregnancy and paediatric oral hygiene course should be on the to-do list for dental nurses in a COVID-19 world